ShET TILIN ÚYRENIWDE ANA TILINIŃ PSIXOLOGIYALÍQ ÓZGEShELIGI - Esbergenova, G.B. (SCIENCE and SOCIETY, 2026)
Psychological aspects of learning a foreign language. The factors influencing on the successful studying of a foreign language are viewed in the article. The author shows their correlation and influence on the process of studying of a foreign language. The methodical and psychological aspects of studying of a foreign language are examined in the article.